2012
DOI: 10.1002/ejoc.201101454
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Cascade Reaction of 4‐Iodopyrazole Derivatives with Amidines for the Synthesis of Pyrazolo[4,3‐d]pyrimidine Derivatives

Abstract: An efficient copper‐catalyzed cascade reaction of 4‐iodopyrazolecarbaldehydes and 4‐iodopyrazolecarboxamides with substituted amidines for the preparation of substituted pyrazolo[4,3‐d]pyrimidines and pyrazolo[4,3‐d]pyrimidin‐7(6H)‐ones, respectively, is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…4‐Iodo‐pyrazole‐3‐carbaldehydes 17 based aldo‐x precursors have also been demonstrated to be viable precursor for the generation of 2 H ‐pyrazolo[4,3‐ d ]pyrimidines 101 by using C‐N coupling reaction with substituted amidines 100 (Scheme 20). [ 40 ] L‐proline was found to be a suitable ligand for this Cu‐catalyzed cascade transformation which delivered the pyrazolo[4,3‐ d ]pyrimidines 101 in excellent yields (84%‐85%). It was also observed that substitution pattern in pyrazole ring did not have any significant impact on the outcome of the reaction.…”
Section: Copper‐catalyzed Approaches For the Synthesis Of Pyrazole Fumentioning
confidence: 99%
“…4‐Iodo‐pyrazole‐3‐carbaldehydes 17 based aldo‐x precursors have also been demonstrated to be viable precursor for the generation of 2 H ‐pyrazolo[4,3‐ d ]pyrimidines 101 by using C‐N coupling reaction with substituted amidines 100 (Scheme 20). [ 40 ] L‐proline was found to be a suitable ligand for this Cu‐catalyzed cascade transformation which delivered the pyrazolo[4,3‐ d ]pyrimidines 101 in excellent yields (84%‐85%). It was also observed that substitution pattern in pyrazole ring did not have any significant impact on the outcome of the reaction.…”
Section: Copper‐catalyzed Approaches For the Synthesis Of Pyrazole Fumentioning
confidence: 99%
“…[3b] Because we knew the optimized conditions for the anticipated coupling reaction, [4] we simultaneously investigated the reaction of 3-haloindole-2-carbaldehyde 1 with guanidine hydrochloride (2), formamidine acetate (3), acetamidine hydrochloride (4), and benzamidine hydrochloride (5). [3b] Because we knew the optimized conditions for the anticipated coupling reaction, [4] we simultaneously investigated the reaction of 3-haloindole-2-carbaldehyde 1 with guanidine hydrochloride (2), formamidine acetate (3), acetamidine hydrochloride (4), and benzamidine hydrochloride (5).…”
Section: Resultsmentioning
confidence: 99%
“…[2] Amongst these approaches, transitionmetal-catalyzed processes have proved complementary to the conventional protocols and have allowed the reactions to be performed under relatively mild conditions. [4] Essentially, to extend the scope of this protocol, we envisage that reacting guanidine or substituted amidines with 3-haloindole-2-carbaldehydes under identical conditions should lead to 2-substituted 5H-pyrimido [5,4-b]indoles (Figure 1), which is the core framework of compounds associated with a variety of biological properties such as PDE inhibition, ionotropic and chronotropic activities, and benzodiazepine receptor binding activity. [3] More recently, we reported a facile and efficient synthesis of pyrazolo [4,3-d]pyrimidines through a copper-catalyzed cascade reaction between 4-iodopyrazole-3-carbaldehydes and substituted amidines.…”
Section: Introductionmentioning
confidence: 99%
“…In the first phase of the study we investigated the strategy with the heteroarylation of allylpyrroles that can be readily prepared from primary allylamines. We commenced our studies with the stereoselective synthesis of primary allylamines 2a – i from MBH acetates 1a – i of 4‐iodo‐3‐pyrazolecarbaldehydes according to the reported procedure 3c. Because ( E ) stereochemistry on the substrates is required for the anticipated intramolecular heteroarylation, we performed the studies with derivatives generated from acrylates only.…”
Section: Resultsmentioning
confidence: 99%